Why Isn't Nurse Staffing Evaluated as Part of Hospital Accreditation and Quality Designations?. Issue 1 (January 2023) - Simpson, Kathleen Rice
Abstract : The Centers for Medicare and Medicaid Services and the Joint Commission have announced two new designations for hospitals with maternity services. When the public sees that hospitals are designated as providing high quality maternity services, there is an assumption that there are enough nurses to care for the childbearing family from admission to discharge. It is well known that adequate nurse staffing in linked to less risk of inpatient morbidity and mortality, yet neither of these new designations include nurse staffing as part of the criteria.